TINJAUAN ULANG KINERJA SIMPANG BERSINYAL PADA SIMPANG KISARAN MEULABOH - Meidia Refiyanni; Lissa Opirina (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
As the population increases and the growth of vehicles especially in urban areas causes traffic crowds. Roads are a very important means of land transportation to consider in order to support the progress of an urban area. Increasing the volume of traffic on urban roads, especially in the city of Meulaboh precisely deviated from the range caused by the increasing growth of traffic vehicles, especially during rush hour. Kisaran intersection connects Sisimangaraja road to Gajah Mada street, from Gajah Mada road heading Manekro road, and from Imam Bonjol road toward Sisimangaraja road. This intersection is one of the roads that is always crowded and very strategic and is used as access to get to the city center. Re-evaluate the performance of the signal intersection to find out the capacity, degree of saturation, delay, length of the queue and the number of stalled vehicles, which is based on the current traffic volume. The problem to be raised and also the purpose of this study is to determine the performance of the intersection of the Intersection Junction based on current traffic flow conditions. The method used is the Indonesian Road Capacity Manual Method 1997. Based on the results of the analysis of calculations, the volume of traffic flow of Manekro 3218 pcu / hour with a capacity of 1963 pcu / hour, Imam Bonjol road 2855 pcu / hour with a capacity of 1741 pcu / hour, Sisimangaraja road 2981 pcu / hour with a capacity of 1818 pcu / hour and the Gajah Mada road. Keywords: Evaluation, Signalized Intersection, Intersection Performance